The role of community services in supporting micro, small and medium enterprises (MSMEs) in the sub-district Palampang, Rilau Ale District Bulukumba Regency - Faidah, Nurfaidah; Rusdiah; Bunyamin; Hadidu, Andi (Institute of Education and Social Research, 2023)
In implementing the sub-district's financial management seminar program and MSME support (digital-based businessdevelopment) activities, this is a program carried out by the STIE – YPUP Makassar Community Service Team, which provides extensive insight to the sub-district's personnel. It is intended to. Efforts to manage sub-district finances. Mean while, MSME support it self is carried out to improve the digital-based economy of the community. The methods used were focus group discussions (FGD) and visits to community business facilities. Conclusion The results show that the factors and causes related to the economy of the community of Palampang village were found. Business development seminars (online business) utilizing digital technology will expand the scope of product marketing for community businesses and have a positive impact on business development.